Fuzzy model to assess the water quality in the Meia Ponte river watershed under different standpoints - Patto, Vinícius Sebba; Cruz Junior, Gelson da; Bini, Luis Maurício; Oliveira, Marco Antonio Assfalk De (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2009: Anais do I Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2009)
This paper addresses a fuzzy model to assess the quality of the water through the use of three different indices. To compose these indices, we considered the use of the water and the characteristics of the Meia Ponte river watershed. At first, we will present the context, the assessment of water quality considering the complexity of the water, its parameters, and its application, as well as the non-significant relationship between parameters employed to assess its quality. Our main goal is to help the assessment of water quality, avoiding the influence of parameters on each other and taking into account the destination of the water. Then, we will present the model and the fuzzy inference process. At the end, a case study is presented in order to help to compare the results of the three proposed indices with the results obtained from the classical model proposed by the National Sanitary Foundation of the United States to determine the index of the water quality. To finish, we discuss it.